Diagnostic staging laparoscopy in gastric cancer treatment: A cost‐effectiveness analysis. Issue 6 (4th December 2017) - Li, Kevin; Cannon, John G.D.; Jiang, Sam Y.; Sambare, Tanmaya D.; Owens, Douglas K.; Bendavid, Eran; Poultsides, George A.
Abstract : Background and Objectives: Accurate preoperative staging helps avert morbidity, mortality, and cost associated with non‐therapeutic laparotomy in gastric cancer (GC) patients. Diagnostic staging laparoscopy (DSL) can detect metastases with high sensitivity, but its cost‐effectiveness has not been previously studied. We developed a decision analysis model to assess the cost‐effectiveness of preoperative DSL in GC workup. Methods: Analysis was based on a hypothetical cohort of GC patients in the U.S. for whom initial imaging shows no metastases. The cost‐effectiveness of DSL was measured as cost per quality‐adjusted life‐year (QALY) gained. Drivers of cost‐effectiveness were assessed in sensitivity analysis. Results: Preoperative DSL required an investment of 107 012 per QALY. In sensitivity analysis, DSL became cost‐effective at a threshold of 100 000/QALY when the probability of occult metastases exceeded 31.5% or when test sensitivity for metastases exceeded 86.3%. The likelihood of cost‐effectiveness increased from 46% to 93% when both parameters were set at maximum reported values. Conclusions: The cost‐effectiveness of DSL for GC patients is highly dependent on patient and test characteristics, and is more likely when DSL is used selectively where procedure yield is high, such as for locally advanced disease or in detecting peritoneal and superficial versus deep liver lesions.